Pengaruh Kompensasi, Motivasi terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervning di Balai Besar Kesehatan Paru Masyarakat Surakarta - SUDARTONO, SUDARTONO; , Dr. Triyono, S.E., M.Si; , Ihwan Susila, Ph.D (2016)
Abstract The purpose of this research is to present a model that examined the effect of compensation, motivation, job satisfaction, and employee's performance. Data were collected using a questionnaire of eighty employees from The Centre of Public Healty Pulmonary Surakarta. A simple random sampling technique used in this study. The authors tested the direct effects and the mediation effect using GSCA (Generalized Structure Component Analysis). The results showed that compensation and employee's motivation have positive effect on job satisfaction. Compensation and employee's motivation also have positive effect on employee's performance but not mediated by job satisfaction. The implication of this study discussed in this article.